Estudo in silico de diterpeno e alcaloide com potencial antibacteriano contra klebsiella pneumoniae - Fernandes, Natan Dias (2022)
Klebsiella pneumoniae is a bacterium belonging to the Enterobacteriaceae family, in the form of gram-negative bacilli. It is responsible for several cases of pulmonary and urinary infections that can progress to pyelonephritis, pneumonia or even sepsis in hospital environments. The most affected populations are children and the elderly. Cases tend to be more severe in immunocompromised patients, often leading to death. Approximately 20% of pneumonia cases in american hospitals are caused by Klebsiella pneumoniae. Several classes of antibiotics are used to treat infections. However, the bacterium is resistant to most existing therapies. Thus, the search for new drugs is necessary and in silico methods are important means, given the possibility of predicting the biological activity and physicochemical properties of molecules, contributing to the reduction of costs and time in research. Natural products such as alkaloids and terpenes have been shown to be effective in several studies in the fight against Klebsiella pneumoniae. Therefore, the objective of this work was to find molecules capable of fighting the microorganism through in silico methods, using the virtual screening of structures against an enzymatic target. In this study, a database containing 312 structures was used for virtual screening and the computational methods used were: consensus screening between QSAR (Quantitative Structure-Activity Relationship) models, cytotoxicity risk analysis and molecular docking. Consensual analysis between QSAR models showed satisfactory statistical parameters that indicated molecules with possible activity against topoisomerase IV from Klebsiella pneumoniae. These molecules were immediately analyzed for the risk of cytotoxicity, obtaining two structures that did not present risk: NT48, an alkaloid and NT262, a diterpene. Of the predicted metabolites for the molecules, some demonstrated a low risk of cytotoxicity. In molecular docking, NT48 and NT262 formed significant interactions with amino acid residues of the enzyme, fundamental for its inhibition. Therefore, it is believed that these structures, when demonstrating good performance in the performed screenings, are promising against topoisomerase IV from Klebsiella pneumoniae, showing potential to be analyzed experimentally.